Exploring fungal potential for microbial-induced calcite precipitation (MICP) in bio-cement production - Inderpal Devgon; Rohan Samir Kumar Sachan; Rohan Samir Kumar Sachan; Khushboo Rajput; Mukesh Kumar; Mukesh Kumar; Abdel Rahman Mohammad Said Al-Tawaha; Arun Karnwal; Arun Karnwal; Tabarak Malik (Frontiers in Materials, 2024)
IntroductionMicrobial-induced calcite precipitation (MICP) involves various microorganisms, such as bacteria, fungi, and algae. This study focuses on producing bio-cement using fungal species and selecting potential candidates isolated from alkaline soil of different regions of Punjab, namely, Majha, Malwa, and Doaba.MethodsThe selection of fungi isolates capable of bio-cement production involves several tests, including a urease assay and calcium precipitation. Isolates having high urease enzyme production and the ability to perform calcite precipitation are selected for instrumental analyses such as X-ray diffraction (XRD) and scanning electron microscopy (SEM). The isolates selected for further analysis are S1 (3) with 8.879 ± 2.94 µg/ml, S1 (18) with 8.421 ± 0.13 µg/ml, and S4 (1) with 10.057 ± 0.45 µg/ml urease activity and least free calcium ions that are 2.337 ± 0.5 µg/ml, 3.339 ± 0.5 µg/ml, and 4.074 ± 0.1 µg/ml respectively.Results and discussionCalcite precipitation is confirmed through XRD and field emission scanning electron microscopy (FESEM). XRD images showing calcite precipitation with sharp crystalline peaks for S1 (3), S1 (18), and S4 (1) are shown. The calcite precipitation is evident in the micrographs of FESEM. These combined results confirm the potential of urease-positive fungi to facilitate calcite production, which could lead to bio-cement development in future research.